2019
DOI: 10.31487/j.rdi.2019.04.01
|View full text |Cite
|
Sign up to set email alerts
|

False-Positive Calcifications and Radiation Dose in Coronary Artery Calcium Scoring Using Iterative Reconstruction on The Basis of a Noise Threshold

Abstract: Radiation dose from cardiac CT seems to be underestimated. To determine the effect of iterative reconstruction in coronary artery calcium (CAC) scoring on false positive lesions and radiation dose using a noise threshold. Noise-based thresholds have been previously suggested to reduce false positive lesions in lower dose protocols. In 388 matched pairs of patients we performed CAC scoring using a 320-row CT-scanner with standard dose filtered backprojection (FBP) and lower dose iterative reconstruction (IR). D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
(39 reference statements)
0
1
0
Order By: Relevance
“…Multiple studies have demonstrated the superiority of iterative reconstruction (IR) over filtered back projection (FBP) for noise reduction during image reconstruction [ 39 , 40 ]. One study showed decreased radiation dose, higher signal-to-noise ratio (SNR), and fewer false positive calcifications with low-dose iterative reconstruction by establishing noise thresholds; low-dose IR exhibited better performance than filtered back projection [ 41 ]. Furthermore, DL-based image reconstruction (DLIR) may be an even better alternative to IR and FBP.…”
Section: Towards Clinical Implementationmentioning
confidence: 99%
“…Multiple studies have demonstrated the superiority of iterative reconstruction (IR) over filtered back projection (FBP) for noise reduction during image reconstruction [ 39 , 40 ]. One study showed decreased radiation dose, higher signal-to-noise ratio (SNR), and fewer false positive calcifications with low-dose iterative reconstruction by establishing noise thresholds; low-dose IR exhibited better performance than filtered back projection [ 41 ]. Furthermore, DL-based image reconstruction (DLIR) may be an even better alternative to IR and FBP.…”
Section: Towards Clinical Implementationmentioning
confidence: 99%